Development of the genetic classification of Aegilops columnaris Zhuk. chromosomes based on the analysis of introgression lines Triticum aestivum×Ae. columnaris - A. A. Shishkina; A. Yu. Dragovich; A. S. Rouban; S. N. Sibikeev; A. E. Druzhin; E. D. Badaeva (Вавиловский журнал генетики и селекции)
Aegilops columnaris Zhuk. is a potential source of new genes for wheat improvement. However, this species has not yet been used in practical breeding. In the present work we have for the first time reported the development and molecular-cytogenetic characterization of T. aestivum×Ae. columnaris introgression lines. Analysis has not revealed alien genetic material in five of the 20 lines we have studied, while the remaining lines carried from 1 to 3 pairs of Aegilops chromosomes as addition(s) or substitution(s) to wheat chromosomes. Altogether, five different chromosomes of Aegilops columnaris have been detected in the karyotypes of 15 lines by C-banding and fluorescent in-situ hybridization (FISH). Based on substitution spectra, these chromosomes were identified as 3Ае1, 3Ае2, 5Ае2, 6Ае1 and 6Ае2. In addition, another Aegilops chromosome has been found in the line 2305/1 as a monosomic addition; due to the lack of group-specific markers we were unable to assign this chromosome to a particular genome or a genetic group and therefore it was designated Ае-а. In several lines acrocentric and telocentric chromosomes have been revealed (Ae-b and Ae-c). It is most likely that these chromosomes were derived from unknown Aegilops chromosomes due to a large deletion. A comparison of electrophoretic spectra of gliadins in introgression lines L-2310/1 and L-2304/1 with substitutions of chromosome 6D with two different chromosomes of Ae. columnaris (these lines were assigned to the 6th homoeologous group based on C-banding data) has shown that they carry different alleles of the gliadin loci. This observation confirmed that lines L-2310/1 and L-2304/1 contained non-identical 6Ae chromosomes. Taking into consideration our previous results of FISH analyses, three other Ae. columnaris chromosomes can be assigned to homoeologous groups 1, 5 and 7 of the U-genome based on the location of 5S and 45S rDNA loci (1U and 5U) or pSc119.2 probe distribution (7U). Thus, based on our current data as well as on the results of earlier work, we can identify eight out of the 14 chromosomes of Aegilops columnaris.